2013
DOI: 10.3109/11038128.2012.752031
|View full text |Cite
|
Sign up to set email alerts
|

Managing critical incidents in grocery shopping by community-living people with Alzheimer's disease

Abstract: In conclusion, it is important that relatives and professionals take into account relevant actions to help people with AD coordinate with their environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 30 publications
3
38
0
3
Order By: Relevance
“…Differences were found regarding 5 of 13 types of services in the personal care category. The finding that clients with cognitive impairment were granted more services than clients without cognitive impairment might not be surprising because they often need support for managing daily living (Brorsson et al, ; Sandberg et al, ). Furthermore, persons with dementia, who live at home, are exposed to risks in daily life (Gilmour, ; Lach & Chang, ; Sandberg et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences were found regarding 5 of 13 types of services in the personal care category. The finding that clients with cognitive impairment were granted more services than clients without cognitive impairment might not be surprising because they often need support for managing daily living (Brorsson et al, ; Sandberg et al, ). Furthermore, persons with dementia, who live at home, are exposed to risks in daily life (Gilmour, ; Lach & Chang, ; Sandberg et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive impairment may have a strong impact on daily life, for example, for persons with dementia. Daily‐living activities (e.g., shopping, moving outdoors) might be difficult to do independently (Brorsson, Öhman, Cutchin, & Nygård, ; Sandberg, Rosenberg, Sandman, & Borell, ). Dementia involves reduced cognitive capacity such as impaired memory and often also the ability to communicate.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining 28 articles were read thoroughly to identify articles that provided information of direct relevance to the construction of a tool for auditing the quality of public buildings and spaces likely to be used by people with dementia. Fifteen such articles were identified (Andrews, 2006;Blackman et al, 2003;Boex and Boex, 2012;Brorsson et al, 2013;Brorsson et al, 2011;Burton, 2012;Burton et al, 2004;Crampton and Eley, 2013;Keady et al, 2012;McCabe and Sim, 2006;Mitchell and Burton, 2010;Mitchell et al, 2004;Mitchell et al, 2003;Topo and Kotilainen, 2009;van Schaik et al, 2008) including a review of the literature by Keady et al (Keady et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In the field of dementia research, much of the focus has been on wandering and getting lost in public spaces outdoors (Bantry White & Montgomery, 2016; Lai & Arthur, 2003). Research has demonstrated that being active and able to come out to use public spaces in the neighbourhood increases independence, especially for older people and those living with dementia (Argyle, Dening, & Bartlett, 2017;Brittain, Degnen, Gibson, Dickinson, & Robinson, 2017;Brorsson, Ö hman, Cutchin, & Nygård, 2013;Burton & Mitchell, 2006;Nygård, 2006). Nonetheless, questions about accessibility within public spaces have been discussed, including how people living with dementia independently navigate and find their way through local public spaces (Blackman, Van Schaik, & Martyr, 2007;Burton & Mitchell, 2006;Mitchell & Burton, 2010;Mitchell, Burton, & Raman, 2004).…”
Section: Public Spaces In the Context Of Dementiamentioning
confidence: 99%